ANALISIS PENGARUH RISK PERCEPTION, RISK TOLERANCE, OVERCONFIDENCE, DAN LOSS AVERSION TERHADAP KEPUTUSAN INVESTASI GENERASI MILIENIAL - Tubastuvi, Naelati; Azzahara, Cantik Tiara Maharani; Purwidianti, Wida; Bagis, Fatmah (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
This study aims to determine the factors that influence investment decision making for millenial generation in Cilacap, Central Java. The research use quantitive method with primary data collected by distributing questionnarires. The millenial generation in Cilacap is the population in this study with sample used is 101 respondents. Data was analyzed using IBM SPSS Statistics 20. The result show that Risk perception and loss aversion influences the investment decision of the millenial generation in Cilacap. This means that the higher person perception of risk and loss aversion, the more careful the person will tend to be in making investment decision. Meanwhile, risk tolerance and overconfidence does not influence the investment decision of the millenial generation in Cilacap